Pengaruh Thin Capitalization, Beban Pajak Tangguhan, Transfer Pricing dan Manajement Laba Terhadap Penghindaran Pajak (Studi Empiris Pada Perusahaan Sektor Pertanian yang Terdaftar di BEI Periode 2020-2022) - Farhan Azmi Asavandra; Einde Evana; Tri Joko Prasetyo; Kamadie Sumanda Syafis (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This research aims to determine the influence of thin capitalization, deferred tax burden, transfer pricing, and earnings management on tax avoidance practices in agricultural sector companies listed on the IDX for the 2020-2022 period. The research method used involves the use of statistical regression to measure the relationship between these variables. The results of the analysis show that thin capitalization and deferred tax expenses have a significant positive influence on tax avoidance practices, transfer pricing has a significant negative influence on tax avoidance practices while earnings management has no influence on tax avoidance. Understanding these factors influences company decisions in managing the Company's financial operations for more effective prevention and control. In conclusion, this research highlights the importance of paying attention to the relationship between thin capitalization, deferred tax burden, transfer pricing, and earnings management in the context of corporate tax avoidance.